Chinese university patenting, patent commercialization and economic growth: A provincial-level analysis. Issue 2 (3rd July 2019) - Luan, Chunjuan; Song, Bowen
Abstract : Though many of previous studies argue the connection or the relationship between economic growth and patents, however, the extant findings are still limited. This paper aims to investigate the mutual impact between Chinese university patenting (CUP) and Gross Regional Domestic Product (GRDP) by selecting the indicators of correlation coefficient. The provincial-level distribution both for Chinese university granted invention patents (CUGIPs) and commercialized patents of CU-GIPs, as well as patent value for each prolific province, are analyzed and compared. Results show that GRDP has very high positive influence on CUP; on the contrary, this influence is not so high though it is positive. The features of highly centralized and very uneven distribution of CUGIPs and commercialized patents of CUGIPs are also disclosed. As far as patent value concerned, the mean values of Beijing and several southern provinces tend to be much higher than those of northern provinces. The analyses carried out in this paper allow several potential applications and extensions in the field of university patenting, patent commercialization and economic growth.